2017
DOI: 10.7717/peerj.3768
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, physical function and general health markers of Masters athletes: a cross-sectional study

Abstract: Once the general decline in muscle mass, muscle strength and physical performance falls below specific thresholds, the middle aged or older adult will be diagnosed as having sarcopenia (a loss of skeletal muscle mass and strength). Sarcopenia contributes to a range of adverse events in older age including disability, hospitalisation, institutionalisation and falls. One potentially relevant but understudied population for sarcopenia researchers would be Masters athletes. Masters sport is becoming more common as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
(51 reference statements)
3
13
0
Order By: Relevance
“…When compared to the Schienkiewitz et al (2017) BMI data, it was apparent that Master Athletes (75%) and sedentary controls (50%), but not nuns/monks (40%) have a higher proportion of individuals with a BMI indicative of underweight or normal compared to the general German population in this age group (40%). Such results were similar with previous research that demonstrated a healthy BMI in Master Athletes (Fien et al, 2017) and nuns/monks (Bennett et al, 2018). Another essential aspect of preserving health and function in older adults is the ability to maintain muscle mass and power.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When compared to the Schienkiewitz et al (2017) BMI data, it was apparent that Master Athletes (75%) and sedentary controls (50%), but not nuns/monks (40%) have a higher proportion of individuals with a BMI indicative of underweight or normal compared to the general German population in this age group (40%). Such results were similar with previous research that demonstrated a healthy BMI in Master Athletes (Fien et al, 2017) and nuns/monks (Bennett et al, 2018). Another essential aspect of preserving health and function in older adults is the ability to maintain muscle mass and power.…”
Section: Discussionsupporting
confidence: 93%
“…Inspection of other health-related indicated that only 1.7% of our sample took three medications per day, and 3.3% had a GDS score of 5. 40% of the sedentary controls and 30% of the nuns/monks are engaged in exercise once or twice a week for at least 30 min; Master Athletes exercise twice (45%), three (35%) or five times (20%) a week for at least 60 min, which is similar to data reported by Fien et al (2017). Eighty-five percent of the group of nuns/monks report daily leisure or gardening activities for at least 30 min each day; Master Athletes as well as sedentary controls are less active with 65%, respectively 50%.…”
Section: Discussionsupporting
confidence: 79%
“…This prevalence for sarcopenia is substantially lower than the 1-29% reported rates for community dwelling adults over the age of 50 years (39). A similar study by Fien, Climstein (40) found that in a cohort of 156 Master's athletes, 3.8% were considered to be below the sarcopenic HGS cut-off points. The difference in results is likely due to the larger sample size and the higher level of training of the Masters' athletes compared to the more recreationally active older adults used in the current study.…”
Section: Discussionmentioning
confidence: 81%
“…Physical activity has been shown to contribute substantially to the maintenance of the individual physiological and psychological well-being in all phases of life [3]. In the elderly, physical exercise can slow down or even reverse the trend towards sarcopenia [4,5]. However, which kind of physical activity could provide the more beneficial effects is still unclear and needs to be studied in depth [3].…”
Section: Introductionmentioning
confidence: 99%